HIV/AIDS statistical analysis and morbidity prediction among injection drug users in the Black Sea region of Ukraine - Talalaev, K. O.; Hoydyk, V. S.; Vastyanov, R. S.; Todorova, A. V. (Journal of Education, Health and Sport, 2019)
The development of methods for statistical analysis of large data volumes and availability of standard information processing packages to users shows signs of widespread their usage, including for medical forecasting. It is a scientifically sound prediction of possible future changes in public health in general or the health status of specific patients. In order to make medical decisions and obtain information about public health in general or the health of individual patients the prediction of possible future changes is important. Different statistical approaches should be applied to validate the projected risks. Comparatively two study groups tested for normality a number of criteria presented for analysis and concerning the incidence of human immunodeficiency virus/acquired immunodeficiency syndrome of residents of Odessa, Mykolaiv, Kherson regions and Ukraine as a whole, as well as injecting drug users, injecting drug users specified areas. Using the modern methods of a statistical analysis the authors come to the idea that these absolute and relative data allow to make a complex scheme of HIV/AIDS prediction on the Black Sea region of Ukraine. Therefore, it was shown that Odessaand Khersonregions of the Black Searegion demonstrated a steady increase in the HIV incidence; the increase of the incidence makes around 10-20% annually. In the Mykolaiv region, on the contrary, there is an annual reduction in incidence, although this trend weakened in recent years. The nature of fluctuations in the incidence of HIV in the period from 2006 to 2018 differs in Odesa, Mykolaiv, Khersonregions and in Ukrainein general. The correlation between Odesa and Mykolaiv region – is negative, between Odessaand Kherson- almost zero between Ukraineand Odessaregion – weakly positive